PENGARUH MODEL PEMBELAJARAN DISCOVERY LEARNING MENGGUNAKAN MEDIA VIDEO TERHADAP HASIL BELAJAR KIMIA - Rahmadini, silvia (Jurnal Pendidikan Teknologi Informatika dan Sains, 2024)
Education is one of the most important things in human life, because through education will create people who are potential, creative and have bright ideas as provisions to get a better future. Quantitatively, it can be said that education in Indonesia has progressed. Education is also a conscious effort that is deliberately designed to achieve the goals that have been set. One of the goals of education is to improve the quality of human resources. Through good education, we will easily follow developments in the future, especially developments in the field of Science and Technology (IPTEK). Quasi-experimental research design (Experimental Design). This research is quantitative, and uses statistical techniques to analyze numerical data (numbers) using SPSS (Statistical Product and Service Solutions). This study used an experimental research design known as Nonequivalent Control Group Design. Pretest and posttest were used in the experimental and control groups of these investigations. All grade X students in Science SMAN 17 Pekanbaru are the total population. The sample used a maximum of two classes: class X Science 1, which has 25 students as an experimental class, and class X Science 2, which has 25 students as a control class. Based on the results of research conducted thoroughly supported by accurate data that there is an influence of the Discovery Learning learning model on student learning outcomes on redox reaction material in Class X of SMAN 17 Pekanbaru, this is according to the results of the t test calculation, where t calculate the table > t (3.126>2.01) and ρ value (0.003) < 0.05 at a significance level of 5%. While the results of the average score study showed that the results obtained for the final ability of the experimental group with the Discovery Learning Learning Model were obtained on average 78.85 and for the control group with conventional methods obtained an average of 74.62, it was concluded that there was a significant difference between the average score of the experimental class and the average value of the control class of 42.3%.